2019
DOI: 10.1111/dpr.12399
|View full text |Cite
|
Sign up to set email alerts
|

Over‐indebtedness and microcredit in Cambodia: Moving beyond borrower‐centric frames

Abstract: Over the past two decades, Cambodia has experienced an unprecedented credit boom, a growth in lending so rapid that the International Monetary Fund (IMF) referred to it as "one of the fastest financial deepening episodes by historical crosscultural standards" (IMF, 2016, p. 4). This deepening has been driven by the expansion of microcredit. In tandem, over-indebtedness has increased among microcredit borrowers, and debt has become a significant political and economic concern. This article explores how over-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…According to [58], after availing microcredit, the borrowers contributed to their family incomes much more significantly than non-borrowers. The study in [59], on the other hand, warns against the negative impacts of microcredit with regard to incurring unbearable levels of debt. Thus, to convert small borrowers into large borrowers for different types of ventures, it is very important to increase the loan quantum and enhance the knowledge and skill in management.…”
Section: Discussionmentioning
confidence: 99%
“…According to [58], after availing microcredit, the borrowers contributed to their family incomes much more significantly than non-borrowers. The study in [59], on the other hand, warns against the negative impacts of microcredit with regard to incurring unbearable levels of debt. Thus, to convert small borrowers into large borrowers for different types of ventures, it is very important to increase the loan quantum and enhance the knowledge and skill in management.…”
Section: Discussionmentioning
confidence: 99%
“…Critics must better attend to those varied institutional landscapes, underpinned by specific social norms and historical practices (Guérin and Kumar, 2017), in order to identify appropriate reforms likely to succeed in regulating microfinance. A first place to start would be to ‘move beyond borrower‐centric frames’ of over‐indebtedness (Bylander et al., 2019: O154), such as explaining multiple borrowing as an outcome of naïve decision making (Arnold and Booker, 2013). Such apolitical arguments, devoid of the diverse power relations that constitute microfinance markets, are likely to blame borrowers who are navigating economic transformations often stacked against them.…”
Section: Resultsmentioning
confidence: 99%
“…While the microfinance industry has lauded self‐regulation as an efficient, market‐based method to expand formal financial services, critical scholarship has demonstrated that self‐regulated microfinance markets have actually exacerbated problems of over‐indebtedness (Afonso et al., 2017; Bylander et al., 2019). The main problem is that compliance with consumer protection principles is entirely voluntary.…”
Section: Regulating Neoliberal Microfinancementioning
confidence: 99%
See 2 more Smart Citations